Two New Species of Crayfish of the Genus Cherax (Crustacea, Decapoda, Parastacidae) from Western and Eastern Indonesian New Guinea - Christian Lukhaup; Rury Eprilurahman; Thomas von Rintelen (Arthropoda)
Two new species of the genus Cherax are described and illustrated. Cherax rayko n. sp., endemic to the Bian River drainage basin in the Muting District, in the northern part of the Merauke Regency, South Papua, Indonesia, is described, figured, and compared with its closest relatives, Cherax alyciae, Lukhaup, Eprilurahman & von Rintelen, 2018, and Cherax peknyi Lukhaup & Herbert, 2008. The new species may be easily distinguished from both by the shape of the rostrum, the shape of the chelae, the shape of the scaphocerite, and the coloration. Cherax phing n. sp., endemic to the Kali Ombak River drainage basin in the western part of the Kepala Burung (Vogelkop) Peninsula, Southwest Papua, Indonesia, is described, figured, and compared with its closest relatives, Cherax pulcher Lukhaup, 2015a, Cherax boesemani Lukhaup & Pekny, 2008, Cherax wagenknechtae Lukhaup and Eprilurahman, 2022, and Cherax gherardii Patoka, Bláha & Kouba, 2015. The new species may be easily distinguished from the latter species by the shape of the chelae, rostrum, and body and by the coloration. A molecular phylogeny based on a mitochondrial gene fragment, 16S, supports the morphology-based description of the two new species, which can also be clearly distinguished by sequence differences.